2022
DOI: 10.1002/advs.202202144
|View full text |Cite
|
Sign up to set email alerts
|

General Strategy toward Hydrophilic Single Atom Catalysts for Efficient Selective Hydrogenation

Abstract: Well dispersible and stable single atom catalysts (SACs) with hydrophilic features are highly desirable for selective hydrogenation reactions in hydrophilic solvents towards important chemicals and pharmaceutical intermediates. A general strategy is reported for the fabrication of hydrophilic SACs by cation-exchange approach. The cation-exchange between metal ions (M = Ni, Fe, Co, Cu) and Na + ions introduced in the skeleton of metal oxide (TiO 2 or ZrO 2 ) nanoshells plays the key role in forming M 1 /TiO 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Ion-exchange strategies can successfully introduce metal elements into frameworks or polymers such as organic metal backbones (MOFs). 106–108 Metal ion precursors with framework or polymer as carriers are adsorbed or ion-exchanged with cations (Zn 2+ , Na + , K + , H + ) by impregnation and finally treated by high-temperature calcination to form SACs with unique coordination structures. 109,110 MOFs have advantages that cannot be compared to other polymers, such as well-defined metal nodes, well-developed pore structures, and tunable organic ligands, and therefore, play a non-negligible role in CO 2 RR.…”
Section: Recent Progress In Sacs For the Co2rrmentioning
confidence: 99%
“…Ion-exchange strategies can successfully introduce metal elements into frameworks or polymers such as organic metal backbones (MOFs). 106–108 Metal ion precursors with framework or polymer as carriers are adsorbed or ion-exchanged with cations (Zn 2+ , Na + , K + , H + ) by impregnation and finally treated by high-temperature calcination to form SACs with unique coordination structures. 109,110 MOFs have advantages that cannot be compared to other polymers, such as well-defined metal nodes, well-developed pore structures, and tunable organic ligands, and therefore, play a non-negligible role in CO 2 RR.…”
Section: Recent Progress In Sacs For the Co2rrmentioning
confidence: 99%
“…Moreover, the combination of experiment and theory revealed that the benzene oxidation on the S, N dual-coordinated Cu SACs had an inferior activation energy barrier. Wu's group 73 also fabricated M SACs (M = Ni, Fe, Co, Cu) on the metal oxide (TiO 2 or ZrO 2 ) supports by the cation-exchange between metal ions and Na + ions introduced in the skeleton of nanoshells under mild conditions (Fig. 5f).…”
Section: Synthetic Strategies Of Single-atom Catalystsmentioning
confidence: 99%
“…• Carbon/Graphene [74,101,143,214,230,236,353] • Carbon nitride [101,[365][366][367] • CeO 2 [368] • Hydroxyapatite [369,370] • Ball milling [353] • Coordination site strategy [370] • Co-precipitation [368] • Electrochemical method [230] • CO 2 methanation [220] • CO 2 RR [74,101] • Cross-coupling [367] • Dry reforming [164,368,369,371] (continued on next page) reused more than six times TPD cycles with constant selectivity of butadiene to butene (~25%) as shown in Fig. 19(a) [257] In order to demonstrate the hydrogenation capability of the Pt-Cu SAC in different stressful conditions (with impurities), the authors tested the SAC in the presence of excess propylene and found that the propylene has no significant effect on the activity and selectivity of hydrogenation • TiO 2 [370] • Y 2 O 3 [220] • ZnO [361] • ZrO 2 [86] • Facile method [371] • Ion-exchange method [86] • Low temperature-induced strategy [220] • Mass-selected soft-landing [236] • Microwave-assisted method [367] • Pyrolysis-assisted method [101] • SEA [164,369] • Sol-gel method…”
Section: Research Advances Of Sacs Used For Selective Hydrogenationmentioning
confidence: 99%
“…Their applications have been extended to non-oxidative CH 4 conversion using Fe 1 /SiO 2 [61]; HER with Co 1 on N-doped graphene [59], graphitic carbon nitride [62], N-doped graphyne [63], and Ni 1 on α-SiX (X = N, P, As, Sb, Bi) [64]; ethylene benzene oxidation using Co 1 /CN [65]; electrocatalytic ethanol oxidation using a hybrid material of Pd nanoparticles and Ni 1 single atom [66]; oxidative desulphurization with Cr 1 /multiwalled carbon nanotubes [67]; CO oxidation using Ni 1 over FeO x [68], phosphorene nanosheet [69], Sc 1 and Fe 1 on honeycomb borophene/Al (111) heterostructure [70], and Ti 1 on MXene [71]; acetylene hydration using Zn 1 with S/N co-doped defective graphene supports [72]; the electrochemical CO 2 RR with Ni 1 on N-doped porous carbon [73], graphene nanosheets [74], carbon black [75] and other ZnN 4 -based SACs [76]; CO 2 hydrogenation with various non-noble metal-based SAC (Mn 1 , Fe 1 , Co 1 , Mo 1 ) supported on graphitic carbon nitride [77]; ORR has been carried out with Co 1 on defective N-doped carbon graphene [78], Fe 1 supported on N-doped porous carbon [79], hierarchically structured porous carbon [80], cellulose-derived nanocarbon [81] and phosphomolybdic acid cluster [82]; and the Oxygen Evolution Reaction (OER) has been carried out on Fe, Co and Ni-based SACs on N-doped graphene [83], N-doped biomass-derived porous carbon [84] as well as γ-graphyne monolayer [85]. Lastly, the production of H 2 O 2 was found to be effective via hydrogenation routes Ni-based SACs [86]. In fact, based on the comparative studies conducted in some of these works, the non-noble metal-based SACs were found to be more attractive and preferable.…”
Section: Introductionmentioning
confidence: 99%